(untitled) (Journal of Comparative Social Work, 2018)
The ways in which care professionals’ support is provided to survivors of femicide, as well as to victims’ families (children, parents and siblings), may be crucial for their process of rehabilitation and integration into society, thereby increasing their chances to live a relatively satisfying life in the future. The objective of this article is to analyse the characteristics of this professional response, and suggest recommendations to enhance the care provided to femicide survivors and their families, in order to make it more significant and context-sensitive. Thus, a qualitative research, including 12 in-depth interviews, was conducted among femicide survivors and family members of femicide victims from the provinces of Imbabura and Carchi in the Ecuadorian highlands. Notwithstanding the governmental efforts, both through legislative changes and the development of care plans for the victims, the findings indicate an ambivalent professional response, as well as a significant lack of support networks for survivors and families of femicide victims.